La géomorphologie glaciaire de la région du mont Tremblant. Deuxième partie : La région de Saint-Faustin – Saint-Jovite - Laverdière, Camille; Courtemanche, Albert (Cahiers de géographie du Québec, 1960)
Glacial tongues, reaching down from the north by way of the valleys on both sides of Mont Tremblant, have spread out in coalescent-lobes in the St. Faustin - St. Jovite bowl and have built up two terminal moraines at Sommet. On and around the site of the Provincial Fish Hatchery at St. Faustin, at least five ice-dammed lakes have been formed between the face of the receding glacier and the natural slope of the ground. The formation of other ice-dammed lakes preceded the establishment of the Rivière Boulé (which had its mouth first at Morrison, then at David sawmill, before settling into its present bed) while the glacial tongue was receding, by phases, from the valley of the Ruisseau des Français. The intermount glacier then caused the retention of two large areas of lake water, in which the plain of St. Jovite was formed before these waters receded as far as Lac à l’Équerre, where the melting of the ice provided a relief of fluvioglacial deposits. Finally, the Champlain Sea was able to stretch out a long arm though the valley of the Rivière Rouge and flood the lower valley of the Rivière du Diable where varved clay and sand have been deposited.